Modifikasi Alat Pelengkung Kayu Skala Pilot dengan Menggunakan Pemanas Modification of Pilot-scale Wood Bending by Heating Elements - Teguh Darmawan; Jayadi Jayadi; Sudijono Sudijono; Ika Wahyuni; Yusuf Amin; Wahyu Dwianto (Masyarakat Peneliti Kayu Indonesia, 2006)
This paper deals with manufacturing and modification of pilot-scale wood bending machine by heating elements. The machine has specifications as follows: 1000 mm width; 1305 mm height; 430 mm and 470 mm radius of upper part and bottom part of bent plates, respectively; and a manual stick pressure with 870 mm length. The upper part and bottom part of bent plates are equipped with heating elements, which the maximum of temperature is arranged to 200°C by the electric force of 220V/2000 watt. Left and right sides of bent plates are covered by 1150 mm x 950 mm insulation board to maintain the heat. From the temperature measurement, the heating plates were reached 50°C in 2.5 minutes, 100°C in 9.5 minutes, and 180°C in 28 minutes. The modified machine has successfuly bent Acacia solid wood with dimensions of 1100 mm(L) x 50 mm(T) and 10 mm, 20 mm, and 30 mm in thickness (R).